Implementasi Komputasi Paralel GPU pada Algoritme Cellular Automata Menggunakan CUDA® - Muhammad Rizal Ma'rufi; Imam Cholissodin; Eriq Muh. Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Video games industry is expanding fast in this modern era. This expansion needs to be balanced with quality and production time from creator. Procedural Content Generation (PCG) is one of innovations that suit with that condition. In PCG world, there are many algorithms can be used, one of the most well know in PCG is cellular automata (CA) algorithm. But CA has efficiency problem, but it can be solved with parallel computing. In this research, parallel computing is implemented using CUDA® technology. But there is another problem, that is the map result from CA is not always giving good result, sometimes it cannot be played due to isolated cave in map, but it can be solved using flood fill algorithm. In this research, the implementation will go through few steps, implementation of CA CPU, CA GPU and Flood Fill. Then those implementations will be integrated with Unity® game engine, then time to implement it to game. The game implementations will use Unity® game engine with C# as scripting language. CA CPU, CA GPU and Flood Fill algorithms computation time will be tested to know their performances. From the test result, CA GPU algorithm has better performance than CA CPU up to 227 times. In the other hand, flood fill algorithm that being used in this research has very high computation time, so the map size is very limited.